2018
DOI: 10.1128/genomea.01497-17
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Trypanosoma cruzi Strain Bug2148

Abstract: Trypanosoma cruzi belongs to the group of mitochondrion-containing eukaryotes and has a highly plastic genome, unusual gene organization, and complex mechanisms for gene expression (polycistronic transcription). We report here the genome sequence of strain Bug2148, the first genomic sequence belonging to cluster TcV, which has been related to vertical transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…For example, while TcI genome sequences from the US or Panama formed single clusters, those from Colombia or Venezuela could be found in very distinct clusters. Finally, whole genome analysis further indicated that the genome of “Bug2148” clearly belonged to TcI, and was more closely related to the Dm28c and SylvioX10 strains ( Figure 1 ), while this strain was initially sequenced as TcV [ 43 ]. On the other hand, strain H1 from Panama was associated with the TcVI DTU cluster rather than to TcI as initially classified [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while TcI genome sequences from the US or Panama formed single clusters, those from Colombia or Venezuela could be found in very distinct clusters. Finally, whole genome analysis further indicated that the genome of “Bug2148” clearly belonged to TcI, and was more closely related to the Dm28c and SylvioX10 strains ( Figure 1 ), while this strain was initially sequenced as TcV [ 43 ]. On the other hand, strain H1 from Panama was associated with the TcVI DTU cluster rather than to TcI as initially classified [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The parasite is predominantly described as diploid, with recently reported haploid genomes of 55 Mb [ 43 ] and 79 Mb [ 44 ] in length from DTUs TcI and TcV, respectively. However, the genome is markedly plastic, with genome size and karyotypic variation between strains, irregular genetic exchange, and reports of widespread aneuploidy [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome from Bug2148 was sequenced with Pacific Biosciences (PacBio) technologies at the Norwegian Sequencing Centre ( www.sequencing.uio.no ), a national technology platform hosted by the University of Oslo and supported by the “Functional Genomics” and “Infrastructure” programs of the Research Council of Norway and the Southeastern Regional Health Authorities 67 . Y strain was sequenced with Illumina MiSeq series by the Genomics facility at the Parque Científico de Madrid (PCM, Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…This could lead to over-, under- or miss-representation of genes or complete chromosomic regions. In this regard, long-read sequencing methods (i.e., PacBio, Nanopore) could be a better choice for the trypanosomatids genomes [ 52 ], as the case of Bug2148 strain [ 53 ]. This technology allows the sequencing of long genetic fragments avoiding the complex and repetitive nature of the parasite.…”
Section: The Genomes Of T Cruzi : a New Updatementioning
confidence: 99%
“…Full length chromosome sequencing was performed with this hybrid strain, using a combined strategy based on bacterial artificial chromosome (BAC) ends sequencing and synteny maps with T. brucei [ 58 ], obtaining 41 virtual chromosomes ( Table 1 ). Despite the continuous re-annotations of these genomes, they are far from being the best reference considering all the new and more completed genomes obtained with current techniques of long and short-read sequencing as Y [ 47 ], Bug2148 [ 53 ], Berenice [ 54 ] or Dm28c [ 55 ] strains. Therefore, we need to pose again which genome is appropriate as a reference for T. cruzi research and if the existence of just one genome reference is useful due to the high heterogeneity of the parasite.…”
Section: The Genomes Of T Cruzi : a New Updatementioning
confidence: 99%